THE LABOR ASPECTS OF UBER AND THE INTERNET OF THINGS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
Abstract: This article will deal with the labor aspects of the Uber service from the internet of things (IoT) context. The understandings about its development and operation will allow the development of a study that clarifythe labor aspects based on Brazilian legislation. Through the methodology of bibliographic and jurisprudential review, the functioning of Uber in Brazil will be presented, and the labor aspects, primarily, the analysis of the possibility or not of recognition of employment ties, aiming to expose and clarify each of these understandings.